MANAGEMENT OF X-RAY EXAMINATION OF COLON IN LOOP WITH CLINICAL COLITIS AT THE RSUD ARIFIN ACHMAD PEKANBARU - Alif Ainus Ibnu Saputra; Darmawan Fitriansyah; Deka Fadhil; Zalia fitri (Medical Imaging and Radiation Protection Research Journal, 2026)
Background: Colon in Loop examination is a lower gastrointestinal radiographic procedure using contrast media to evaluate various colonic abnormalities, including colitis. In clinical practice, the examination protocol may be modified according to the patient's condition and technical challenges encountered during the procedure. One rarely reported situation is the replacement of barium sulfate with a water-soluble contrast medium to obtain optimal visualization of the colon. This study aimed to describe the management of the Colon in Loop radiographic examination in a patient with clinically diagnosed colitis and to explain the rationale for using a water-soluble contrast medium as an alternative when barium sulfate failed to provide adequate diagnostic visualization. Methods: This study employed a case study approach conducted at the Radiology Department of Arifin Achmad Regional General Hospital, Pekanbaru. Data were collected through direct observation, documentation, and interviews with radiographers during the examination procedure. Results: The examination began with a plain anteroposterior (AP) abdominal radiograph, followed by the administration of barium sulfate contrast medium through a catheter and radiographic acquisitions in the left lateral, post-contrast AP, and right posterior oblique (RPO) projections. During the post-contrast AP examination, obstruction of barium sulfate flow was observed in the rectosigmoid region, resulting in suboptimal visualization of the colon. Based on the evaluation by the radiologist and radiographers, the contrast medium was replaced with a water-soluble agent diluted with normal saline (NaCl), allowing the contrast to pass through the obstructed segment and providing improved visualization of the colon.